Pengaruh Harga Terhadap Keputusan Pembelian Pakaian Karawo di Kota Gorontalo: Studi Kasus Rumah Karawo di Kota Gorontalo - Desy Rahmawati Husain; Hapsawati Taan; Citra Aditya Kusuma (Masyarakat Ekonomi Syariah Bogor, 2025)
This research examines how pricing influences consumer decisions for purchasing Karawo in Gorontalo City. The study employed a quantitative approach with data collected through questionnaires and document analysis from a sample of 100 respondents who had previously purchased Karawo. The data were analysed using SPSS software by apllying simple linear regression to determine the relationship between price and purchase decision. The analysis yielded a t-value of 3,919 which exceeds the critical value of 1,660, with a significance level of 0,000 (p < 0,05), thus supporting the hypothesis that price significantly impacts customer’s purchase decision. The coefficient of determination (R2) was found to be 0,207 which indicating that price accounts for 20,7% of the variability in purchasing decisions while the remaining 79,3% is likely influenced by other factors that not included in this study. These findings suggest that although price is a significant determinant, it only partially influences consumer interest in Karawo product.